Microfluidic analysis of seawater-based CO2 capture in an amine solution with nickel nanoparticle catalysts. Issue 53 (November 2021) - Ratanpara, Abhishek; Shaw, Alexander; Thomas, Mallory; Patel, Rajesh N.; Kim, Myeongsub
Highlights: First time Natural seawater based amine solvent was studied as a solution for post carbon-capture in microfluidic device. Seawater with 2.5 (v/v)% MEA absorbs 95.94 % of CO2, which is only 1.79 % less than DI water counterpart. Nickel nanoparticles show excellent catalytic performance for CO2 dissolution in DI water and seawater. A combination of nickel nanoparticles and 2.5 % amine shows 97.05 % CO2 absorption in natural seawater. Abstract: Post-combustion CO2 capture methods like amine scrubbing are currently being utilized to reduce CO2 emissions from fossil fuel power plants. Aqueous monoethanolamine (MEA) solutions are typically used in these processes due to their high CO2 absorption capacity and rapid reaction rate, but these solutions also produce environmentally harmful toxic wastewater and consume large amounts of freshwater. This research analyzes the effectiveness of seawater-based MEA solutions containing nickel nanoparticles (NiNPs) as catalysts, with the goal to minimize the amount of MEA required in the amine scrubbing process and eliminate the use of freshwater. This study is the first to use natural seawater solutions as an alternative to freshwater solutions for CO2 capture. In a microfluidic environment, CO2 microbubbles were generated and their change in size with respect to time was observed to determine the CO2 absorption capacity and rate of the test solutions. Pure seawater demonstrated comparable CO2 absorption to deionized (DI) water. Seawater-based amine solutions absorbed merely 1.79 % less CO2 than DI water-based amine solutions. Seawater-based amine solutions demonstrated faster CO2 absorption rates than their freshwater counterparts. Lastly, to further optimize CO2 absorption, NiNPs were added to each test solution. Seawater with MEA and NiNPs absorbed only 1.15 % less than its DI water counterpart, confirming seawater's potential as amine-based solvent for industrial CO2 capture applications.